Transdifferentiation of erythroblasts to megakaryocytes using FLI1 and ERG transcription factors - Siripin, Darin; Kheolamai, Pakpoom; U-Pratya, Yaowalak; Supokawej, Aungkura; Wattanapanitch, Methichit; Klincumhom, Nuttha; Laowtammathron, Chuti; Issaragrisil, Surapol (Thrombosis and Haemostasis, 2015)
Platelet transfusion has been widely used to prevent and treat life-threatening thrombocytopenia; however, preparation of a unit of concentrated platelet for transfusion requires at least 4–6 units of whole blood. At present, a platelet unit from a single donor can be prepared using apheresis, but lack of donors is still a major problem. Several approaches to produce platelets from other sources, such as haematopoietic stem cells and pluripotent stem cells, have been attempted but the system is extremely complicated, time-consuming and expensive. We now report a novel and simpler technology to obtain platelets using transdifferentiation of human bone marrow erythroblasts to megakaryocytes with overexpression of the FLI1 and ERG genes. The obtained transdifferentiated erythroblasts (both from CD71+ and GPA+ erythroblast subpopulations) exhibit typical features of megakaryocytes including morphology, expression of specific genes (cMPL and TUBB1) and a marker protein (CD41). They also have the ability to generate megakaryocytic CFU in culture and produce functional platelets, which aggregate with normal human platelets to form a normal-looking clot. Overexpression of FLI1 and ERG genes is sufficient to transdifferentiate erythroblasts to megakaryocytes that can produce functional platelets.
Keywords: Transdifferentiation; erythroblast; megakaryocyte; platelet; transcription factors